2016
DOI: 10.1016/j.cmi.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Defining the normal core microbiome of conjunctival microbial communities

Abstract: Bacterial ocular infections are common. Traditional culture and molecular biological methods have obvious limitations to identify the conjunctival microbiota, while metagenomic studies can avoid the defects of these methods. We used the Illumina high-throughput sequencing technology (MiSeq Illumina Sequencing Platform) to sequence the 16S rDNA V3-V4 hypervariable region of all bacteria in conjunctival swab samples. The operational taxonomic units were obtained from the sequences. The bioinformatic analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
167
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 27 publications
17
167
2
3
Order By: Relevance
“…17, 167 This is in sharp contrast to cultures of the lid margin and periocular skin which often grow bacteria. 168, 169 Studies using 16S genomic sequencing have demonstrated an ocular surface microbiome that may have the lowest biomass of any tissue in the body 16, 170, 171 No difference in the quantity and diversity of the ocular microbiome was noted between SS and control subjects; 16 however, significant alterations of the intestinal microbiome were noted in the same cohort with a significant decrease in commensal genera and an increase in pathogenic genera, such as Escherichia/Shigella and Proteobacteria. Mice that had an antibiotic-induced depletion of the microbiome with a cocktail of five oral antibiotics prior to experimental desiccating stress developed significantly worse dry eye than control mice that did not receive antibiotics, suggesting that the intestinal microbiome can modulate ocular surface inflammation and severity of dry eye disease.…”
Section: Dry Eye – a Multifactorial And Self-perpetuating Inflammatormentioning
confidence: 99%
“…17, 167 This is in sharp contrast to cultures of the lid margin and periocular skin which often grow bacteria. 168, 169 Studies using 16S genomic sequencing have demonstrated an ocular surface microbiome that may have the lowest biomass of any tissue in the body 16, 170, 171 No difference in the quantity and diversity of the ocular microbiome was noted between SS and control subjects; 16 however, significant alterations of the intestinal microbiome were noted in the same cohort with a significant decrease in commensal genera and an increase in pathogenic genera, such as Escherichia/Shigella and Proteobacteria. Mice that had an antibiotic-induced depletion of the microbiome with a cocktail of five oral antibiotics prior to experimental desiccating stress developed significantly worse dry eye than control mice that did not receive antibiotics, suggesting that the intestinal microbiome can modulate ocular surface inflammation and severity of dry eye disease.…”
Section: Dry Eye – a Multifactorial And Self-perpetuating Inflammatormentioning
confidence: 99%
“…The PCR amplification was performed as previously described (Hu, Yang, Long, Liu, & Rengel, 2016). The PCR products were confirmed, purified, and quantified as previously described (Huang, Yang, & Li, 2016). The quality and quantity of the amplicon library were assessed on a Bioanalyzer (Agilent, Santa Clara, CA, U.S.A.) and with the Library Quantification Kit for Illumina (Kapa Biosciences, Wilmington, MA, U.S.A.), respectively.…”
Section: Pcr Amplification and 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…It is unclear whether a ‘core’ microbiota persists at the conjunctiva, but profiles closely related to that of the skin have been reported (18). Corynebacterium , Propionibacterium , Staphylococcus and Streptococcus have been consistently dominant, whereas other genera such as Acinetobacter , Brevundimonas , Pseudomonas , Bradyrhizobium , Sphingomonas , Bacillus , Simonsiella and Elizabethkingia have been identified more sporadically (1921). Conjunctival polymicrobial community composition is known to vary with age and season (22) and appears to be responsive to external stimuli such as regular contact lens wear (23).…”
Section: Introductionmentioning
confidence: 99%